Analysis of Per Capita Income towards A Poverty-Free Region in Sampang Regency - Hanafi, Imam; Mustofa, Amirul; Fatah, Zaenal (PT. Anagata Sembagi Education, 2024)
A poverty-free region is one of the seventeen Sustainable Development Goals (SDGs) targets approved by the United Nations in 2015. It aims to end extreme poverty for all people earning less than 1.25 per day and promote inclusive and equitable development. Per capita, income is one of the critical indicators of human resource development and the economy. This research aims to identify economic growth in the context of per capita income and to monitor and evaluate the achievement of the SDGs Without Poverty in the Sampang district. This qualitative study uses a descriptive analysis approach, with data collection methods including observation, documentation, and library research. The research focuses on the achievement of the SDGs Without Poverty indicator, which consists of five key indicators: (i) Percentage of the population living below the national poverty line; (ii) Implementation of the social protection system; (iii) Guarantee of economic resources and fundamental service rights (health, housing, lighting); (iv) Strengthening and development of disaster-resilient areas, and (v) Government policies and proportions in poverty alleviation, as well as several sub-indicators set by the National Development Planning Agency. The study results showed that the increase in per capita income had a negative but insignificant correlation with the poverty rate. However, per capita income positively impacts realizing the SDGs Without Poverty. It has achieved the goal of ending extreme poverty for all people with an income of less than 1.25 per day.